ANALYSIS OF PHYSICO–CHEMICAL PARAMETERS ON PHYTOPLANKTON ABUNDANCE IN THE WATERS OF LABAKKANG DISTRICT, PANGKEP REGENCY - Niartiningsih, Andi; Nawing, Nur Afifa; Samad, Wasir; Yasir, Inayah; Tambaru, Rahmadi (Jurnal Ilmu Kelautan SPERMONDE, 2024)
Pangkep Regency is dominated by pond areas, one of which is located in Labakkang District. These aquaculture activities affect physico-chemical parameters in the waters. This study was aimed to analyze the influence and relationship of physico-chemical parameters on phytoplankton abundance in the waters of Labakkang District, Pangkep Regency. Data were collected using purposive sampling method in several locations, namely waters around river mouths, waters around mangroves, pond discharge waters and waters around docks. The physico-chemical parameters observed include temperature, salinity, nitrate, phosphate, Total Suspended Solid (TSS), carbon dioxide and current velocity. The results showed that the highest phytoplankton abundance was found in the waters around the river mouth with a value of 741 cells/L, while the lowest abundance was found in the pond discharge waters with a value of 154 cells/L. At the station, the highest values were obtained in the temperature parameter of 32,67ºC, nitrate of 0,03 mg/L, phosphate of 0,08 mg/L, TSS of 25,26 mg/L and current speed of 0,25 m/s. The high abundance of phytoplankton is inversely proportional to the salinity level in the water, which is 29%ₒ. The results of the analysis using the one-way ANOVA statistical test showed significant differences in phytoplankton abundance as well as temperature, salinity and TSS parameters between sampling stations. Then multiple regression analysis showed that the most influential parameters on phytoplankton abundance were temperature, nitrate, and TSS with a coefficient of determination of 92,8%. The results of this study can serve as a basis for more effective water management and better environmental monitoring in the context of aquaculture activities in the region.